Pharmacokinetic study of FFP photochemically treated with amotosalen (S-59) and UV light compared to FFP in healthy volunteers anticoagulated with warfarin - Hambleton, Julie; Wages, David; Radu-Radulescu, Lucian; Adams, Melanie; MacKenzie, Malcolm; Shafer, Steven; Lee, Martin; Smyers, Jocelyn; Wiesehahn, Gary; Corash, Laurence (Transfusion (Philadelphia, Pa.), 2002)
BACKGROUND : To date, no clinical trials have characterized FFP infusion efficacy, and infusion still carries infectious risk. This single‐blinded crossover study compared postinfusion kinetics of FVII in photochemically treated FFP to standard FFP. STUDY DESIGN AND METHODS : Subjects donated plasma by apheresis. Half of the collected plasma was treated with the psoralen amotosalen hydrochloride (S‐59) and UVA light, and half were prepared as standard plasma. Subjects received warfarin over 4 days to lower FVII levels. On Day 4, subjects received 1 L of either treated or standard FFP. After 2 weeks, subjects underwent a regimen identical to that with the other type of FFP. RESULTS : After warfarin ingestion, the mean FVII concentration was 0.33 IU per mL. Both types of FFP exhibited comparable FVII kinetics, with a mean peak increment of 0.10 to 0.12 IU per mL occurring at the end of infusion. The effect disappeared after 8 hours. DISCUSSION : Study data of warfarin‐treated healthy volunteers demonstrate that psoralen plus UV‐treated FFP provides an equivalent in vivo coagulation response to control plasma. A 1‐L dose of FFP in adults may provide an initial increment of 0.10 IU per mL of FVII. In the absence of bleeding, FVII levels return to baseline after 8 hours.